Prediction Of Subcellular Localization And Function Of Hypothetical Proteins Of Mycobacterium Tuberculosis H37ra Strain - LAKSHMI PILLAI; USHA CHAUHAN (International Journal of Pharma and Bio Sciences, 2012)
The Tuberculosis is the classical human mycobacterial disease, caused by Mycobacterium Tuberculosis. Mycobacterium tuberculosis is a facultative intracellular pathogen that has evolved the ability to survive and multiply within human macrophages. These bacteria comprise of significant proteins, which involve in the pathogenesis and regulation of cell activity. Thus there arises the need to understand various parameters of these proteins for prediction of their functionality. The computational approaches for prediction of their classes are fast and economical therefore can be used to complement the existing wet lab techniques. Realizing their importance, in this paper an attempt has been made for the insilico prediction of protein subcellular localization and major functions. As in the case of Mycobacterium, proteins are often involved in extensive interactions at various subcellular localizations in cell. Total one thousand four hundred and thirty-two hypothetical proteins of M. tuberculosis were predicted for four locations viz cytoplasmic, integral membrane, secretory protein and protein attached to membrane by Lipid anchor in the subcellular localization. And also major functions like virulence factors, information molecule, cellular process and metabolism molecule were predicted. Such predictions provide a method to annotate Mycobacterium proteomes with subcellular localization and functional information rapidly. And they have widespread applications in function of proteins in the host cell and in designing the tuberculosis drugs.